Thin Film RuO2 Lithiation: Fast Lithium‐Ion Diffusion along the Interface. (9th November 2018) - Kim, Sungkyu; Evmenenko, Guennadi; Xu, Yaobin; Buchholz, Donald Bruce; Bedzyk, Michael; He, Kai; Wu, Jinsong; Dravid, Vinayak P.
Abstract: Although lithium‐ion batteries that run on the conversion reaction have high capacity, their cyclability remains problematic due to large volume changes and material pulverization. Dimensional confinement, such as 2D thin film or nanodots in a conductive matrix, is proposed as a way of improving the cyclic stability, but the lithiation mechanism of such dimensionally controlled materials remains largely unknown. Here, by in situ transmission electron microscopy, lithiation of thin RuO2 films with different thicknesses and directions of lithium‐ion diffusion are observed at atomic resolution to monitor the reactions. From the side‐wall diffusion in ≈4 nm RuO2 film, the ion‐diffusion and reaction are fast, called "interface‐dominant" mode. In contrast, in ≈12 nm film, the ion diffusion–reaction only occurs at the interface where there is a high density of defects due to misfits between the film and substrate, called the "interface‐to‐film" mode. Compared to the side‐wall diffusion, the reaction along the normal direction of the thin film are found to be sluggish ("layer‐to‐layer" mode). Once lithiation speed is higher, the volume expansion is larger and the intercalation stage becomes shorter. Such observation of preferential lithiation direction in 2D‐like RuO2 thin film provides useful insights to develop dimensionally confined electrodes for lithium‐ion batteries. Abstract : The electrochemical lithiation of epitaxial‐grown RuO2 films with different thickness and directions of lithium‐ion diffusion is investigated using the in situ high resolution transmission electron microscopy (HRTEM) technique. The observation of preferential lithiation direction and the different volume expansion in 2D‐like RuO2 thin film provides useful insights to develop dimensionally confined electrodes for lithium‐ion batteries.